Sugarcane/peanut intercropping system improves physicochemical properties by changing N and P cycling and organic matter turnover in root zone soil - Xiumei Tang; Yixin Zhang; Jing Jiang; Xiuzhen Meng; Zhipeng Huang; Haining Wu; Liangqiong He; Faqian Xiong; Jing Liu; Ruichun Zhong; Zhuqiang Han; Ronghua Tang (PeerJ, 2021)
Background The sugarcane/peanut intercropping system is a specific and efficient cropping pattern in South China. Intercropping systems change the bacterial diversity of soils and decrease disease rates. It can not only utilized light, heat, water and land resources efficiently, but also increased yield and economic benefits of farmers. Methods We determined soil nutrients, enzymes and microbes in sugarcane/peanut intercropping system, and analyzed relevance of the soil physicochemical properties and the genes involved in N and P cycling and organic matter turnover by metagenome sequencing. Results The results showed that sugarcane/peanut intercropping significantly boosted the content of total nitrogen, available phosphorus, total potassium, organic matter, pH value and bacteria and enhanced the activity of acid phosphatase compared to monocropping. Especially the content of available nitrogen, available phosphorus and organic matter increased significantly by 20.1%, 65.3% and 56.0% in root zone soil of IP2 treatment than monocropping treatment. The content of available potassium and microbial biomass carbon, as well as the activity of catalase, sucrase and protease, significantly decreased in intercropping root zone soil. Intercropping resulted in a significant increase by 7.8%, 16.2% and 23.0% in IS, IP1 and IP2, respectively, of the acid phosphatase content relative to MS. Metagenomic analysis showed that the pathways involved in carbohydrate and amino acid metabolism were dominant and more abundant in intercropping than in monocropping. Moreover, the relative abundances of genes related to N cycling (glnA, GLUD1_2, nirK), P cycling (phoR, phoB) and organic matter turnover (PRDX2_4) were higher in the intercropping soil than in the monocropping soil. The relative abundance of GLUD1_2 and phoR were 25.5% and 13.8% higher in the IP2 treatment respectively,and bgIX was higher in IS treatment compared to the monocropping treatment. Genes that were significantly related to phosphorus metabolism and nitrogen metabolism (TREH, katE, gudB) were more abundant in intercropping than in monocropping. Conclusion The results of this study indicate that the intercropping system changed the numbers of microbes as well as enzymes activities, and subsequently regulate genes involved in N cycling, P cycling and organic matter turnover. Finally, it leads to the increase of nutrients in root zone soil and improved the soil environment.